The Effect of Laser Ablation Time On The Concentration of Gold Nanoparticle Colloids - Salsa Dila Nisa Pratiwi; Ali Khumaeni; Iis Nurhasanah (Journal of Physics and Its Applications, 2026)
The use of gold nanoparticles is being studied more widely, including in the medical, electronics and sensor fields. Nanoparticles with high concentration and purity can be produced using the pulsed laser ablation method. This study aims to increase the concentration of gold nanoparticle colloids linearly with increasing ablation time using Nd: YAG Laser. The colloid concentration test parameters based on The concentration of AuNPs colloids with 10 minutes, 15 minutes, and 25 minutes ablation time is 5.17; 8.50; and 20.12 mg/L. It can be concluded that the longer ablation time succeeded in increasing the absorbance value and ultimately increasing the concentration of gold nanoparticle colloids. Nanoparticle colloid concentration can be further investigated using synthesis methods other than pulsed laser ablation.